Correction: Crime – Social risk in contemporary society (Vol 7, No 13, p. 84-113, DOI: 10.5937/pol1713084V) - časopisa Politeia, Uredništvo (Politeia, 2017)
Due to a technical mistake, the correct abstract in Serbian language of the article authored by dr. Dragana Vilić "Crime – Social risk in contemporary society"published in the journal Politeia (issue number 13, vol. 7, p.84) was omitted. The Editorial board apologises to the author and our readers. With the consent of the author, we publish the correct summary in Serbian language in this issue: Crime, as a form of violation of law (A. Giddens), is one of the social risks. One of the negative consequences of the development of a modern, global society is the globalization of criminality (M. Kostić & F. Mirić). Criminality can only be discussed with the development and elaboration of the legal system in the modern sense of the word (including criminal law), but in societies there have always been certain types of norms and beliefs that have influenced human behavior and against which (in) correctness (M. Ivanović). Unlike a positive right that cannot fully follow the dynamics of change in society that influence the definition of a crime, sociology should constantly seek new elements that extend this notion (new, unpredictable, unlimited). The paper analyzes the causes of criminality, its distribution, types (violent, property, etc.), relation to other notions (deviance, delinquency and crime) and its consequences in contemporary society, in order to look at the risk of crime, to seek an adequate social response to This negative phenomenon, and provides an analysis of the penal policy and the role of a prison institution for the offender’s conversion (M. Foucault).